2013 IEEE 39th Photovoltaic Specialists Conference (PVSC) 2013
DOI: 10.1109/pvsc.2013.6744861
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel spectroscopic ellipsometry for CdTe Photovoltaics: From real-time monitoring to large-scale mapping

Abstract: Real time spectroscopy ellipsometry (RTSE) has been applied to study the evolution of thin film optical structure during sputter deposition of polycrystalline CdS/CdTe solar cell stacks on transparent conducting oxide (TCO) coated glass substrates optimized for high efficiency. RTSE provides information on (i) interface formation to the underlying high resistivity transparent (HRT) layer during initial CdS growth, (ii) bulk layer CdS growth and its surface roughness evolution, (iii) CdS/CdTe interface formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[7] Consequently, we ascribe the rollover to a potential energy barrier for hole transport from the SWCNT to the TEC 15M. Note that the 100 nm i-SnO 2 layer that is part of the TEC 15M stack can interdiffuse with deposited CdS during the normal high temperature device processing that is used for superstrate devices, [28] while such interdiffusion in not expected in the present case because the CdTe and i-SnO2 layers are physically separated by the SWCNT layer.…”
Section: Resultsmentioning
confidence: 68%
“…[7] Consequently, we ascribe the rollover to a potential energy barrier for hole transport from the SWCNT to the TEC 15M. Note that the 100 nm i-SnO 2 layer that is part of the TEC 15M stack can interdiffuse with deposited CdS during the normal high temperature device processing that is used for superstrate devices, [28] while such interdiffusion in not expected in the present case because the CdTe and i-SnO2 layers are physically separated by the SWCNT layer.…”
Section: Resultsmentioning
confidence: 68%
“…Finally, an additional means of characterizing the optical properties of MZO-containing device structures is expected to be informative toward the refinement of the M-SE and TG-SE models. In previous studies of CdTe device structures incorporating SnO 2 :F as the transparent conducting oxide and SnO 2 as the HRT layer, infrared spectroscopic ellipsometry (IR-SE) measurements were performed at different stages of fabrication to gain insights into the interaction between adjoining layers [ 59 , 60 ]. In these studies, the role of CdS deposition in modifying the underlying SnO 2 :F free electron and defect properties and the role of the intervening SnO 2 in suppressing these interactions can be characterized.…”
Section: Resultsmentioning
confidence: 99%
“…Infrared spectroscopic ellipsometry (IR-SE) data spanning the photon energy range of 0.05 eV to 0.8 eV were acquired and analyzed. [7] Table 3 presents the free carrier parameters as determined from IR-SE data analysis. From ex-situ IR-SE analysis, the enhanced conductivity of the CIS layer due to nitrogen doping could be detected.…”
Section: De-ee0005405mentioning
confidence: 99%
“…[1][2][3] [2] We developed improved methods for process control and monitoring during deposition of the materials we tested. [7,16] We showed that we could determine the current flow pathways in CdTe devices using scanning microwave impedance microscopy, which advances the general understanding of the devices [13,14]. We developed new understanding of electron beam induced current (EBIC) measurements of the devices.…”
Section: Conclusion Of This Workmentioning
confidence: 99%